Pengaruh Inovasi Dan Kualitas Produk Serta Media Sosial Instagram Terhadap Minat Beli Konsumen Resya Cake And Bakery Di Kabupaten Paser - Anugrah Sari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research aims to determine the influence of innovation variables, product quality and Instagram social media simultaneously, partially and dominantly on consumer purchasing interest in Resya Cakes and Bakery in Paser Regency. Product innovation (X1), product quality (X2) and Instagram social media are used as independent variables while consumer purchasing interest (Y) is used as the dependent variable. The research method used is quantitative research. The sampling technique used was simple random sampling with a sample size of 100 respondents. The data analysis technique used is multiple linear regression analysis. The results in this research show that the independent variables have a partial effect, namely innovation of 0.534, product quality of 0.109 and Instagram of 0.104 on the dependent variable consumer buying interest. Simultaneously, it can be seen that the results obtained through F calculation are 519.776 and the probability value is 0.000 and the dominant variable is the product innovation variable with a value of 0.534. The conclusion of this research is that there is a positive and significant influence simultaneously, partially and dominantly between the Innovation, Product Quality and Instagram social media variables on consumer buying interest at the Resya Cake and Bakery Shop in Paser Regency.